Databases, measures to combating crime against works of art - Agata Klimczyk (Kazimierz Wielki University, 2016)
The aim of the work is to discuss selected databases in the context of crime against works of art. The author has used: the method of legal analysis, historical-legal method and literature study. The documentation of  monuments in the form of advanced electronic systems greatly contributes to the protection of monuments. Above aspects  are clearly delineated in the discussed paper.